The Efforts to improve initial numeracy skills through the use of snakes and ladders game media in early childhood - Hizbul Wathoni; Suparmiati Suparmiati; Rosliana R (Sean Institute, 2024)
One of aspect development children must be developed is aspect cognitive especially on ability counting beginning . This research is uplifting problem-related ability counting beginning child age is still low, especially in children 5-6 years old in group B in the Az Zahra Integrated Islamic Kindergarten School (TK) year 2023–2024 teachings with a total of 8 children. The researcher applied to learn in group B kindergarten Islam Integrated Az Zahra year 2023/2024 teachings with different media, i.e., by using game media like snake stairs for activities counting, beginning with variations of different activities every day. This research includes a type of action research with repair in two cycles (practice, reflection, and improvement). Data collection techniques are carried out through documentation and observation. After the research is carried out, it can be concluded that game media snake stairs can be used to upgradeability count beginning child age, specifically group B This can be seen from the percentage level increase in activity results repair that is, in cycles One reached 50% and in cycle two, it reached 87.5%.